Enzymatic assays for the diagnosis of bradykinin-dependent angioedema. - Federica Defendi (Public Library of Science (PLoS), 2013)
Background The kinins (primarily bradykinin, BK) represent the mediators responsible for local increase of vascular permeability in hereditary angioedema (HAE), HAE I-II associated with alterations of the SERPING1 gene and HAE with normal C1-Inhibitor function (HAE-nC1INH). Besides C1-Inhibitor function and concentration, no biological assay of kinin metabolism is actually available to help physicians for the diagnosis of angioedema (AE). We describe enzymatic tests on the plasma for diagnosis of BK-dependent AE. Methods The plasma amidase assays are performed using the Pro-Phe-Arg-p-nitroanilide peptide substrate to evaluate the spontaneous amidase activity and the proenzyme activation. We analyzed data of 872 patients presenting with BK-dependent AE or BK-unrelated diseases, compared to 303 controls. Anti-high MW kininogen (HK) immunoblot was achieved to confirm HK cleavage in exemplary samples. Reproducibility, repeatability, limit of blank, limit of detection, precision, linearity and receiver operating characteristics (ROC) were used to calculate the diagnostic performance of the assays. Results Spontaneous amidase activity was significantly increased in all BK-dependent AE, associated with the acute phase of disease in HAE-nC1INH, but preserved in BK-unrelated disorders. The increase of the amidase activity was associated to HK proteolysis, indicating its relevance to identify kininogenase activity. The oestrogens, known for precipitating AE episodes, were found as triggers of enzymatic activity. Calculations from ROC curves gave the optimum diagnostic cut-off for women (9.3 nmol⋅min(-1)⋅mL(-1), area under curve [AUC] 92.1%, sensitivity 80.0%, and specificity 90.1%) and for men (6.6 nmol·min(-1)⋅mL(-1), AUC 91.0%, sensitivity 87.0% and specificity 81.2%). Conclusion The amidase assay represents a diagnostic tool to help physicians in the decision to distinguish between BK-related and -unrelated AE.